Truth in Incarnation and Eucharistic Repetition: Proportion Between Things and Mind - Brian Douglas (Religions, 2025)
This article argues that truth can be disclosed and found in incarnation and eucharistic repetition in a proportion between things and mind. Truth as a Christian concept is explored in the Gospel of John, and more specifically in the interaction between Jesus and Pilate, where Pilate at Jesus’ trial asks the question: ‘What is truth?’ The work of biblical commentators is examined in relation to truth in John’s Gospel. The importance of the Word made flesh and its eucharistic repetition is seen as central to truth. This is expanded using the concept of non-identical repetition, as discussed by several scholars, including David Ford and Catherine Pickstock, arguing that Jesus Christ in his incarnate form and in eucharistic repetition calls attention to truth as the proportion between things and mind. The implications of an ontological approach, as opposed to an epistemological approach are drawn in relation to eucharistic theology, with reference to signs (things of this world) and reflective processes (mind) in such a way that where there is a proportion between things and mind, truth is disclosed and found in incarnation and eucharistic repetition.